Preclinical development and first-in-human study of ATX-MS-1467 for immunotherapy of MS. Issue 3 (June 2015) - Streeter, Heather B.; Rigden, Rachel; Martin, Keith F.; Scolding, Neil J.; Wraith, David C.
Abstract : Objective: The study was designed to test the efficacy of ATX-MS-1467 in a relevant preclinical model and to assess its safety for the treatment of patients with secondary progressive multiple sclerosis (SPMS). Methods: ATX-MS-1467 was tested for its ability to suppress experimental autoimmune encephalomyelitis (EAE) in the (Ob x DR2)F1 mouse both before and after disease onset. Safety was assessed by clinical assessment, MRI analysis, and the measurement of immune responses to self- and nonself-antigens in patients with SPMS. Results: ATX-MS-1467 displayed a dose-dependent inhibition of EAE and was more effective than glatiramer acetate in the treatment of ongoing disease in humanized mice. A phase 1 open-label dose-escalating study demonstrated that ATX-MS-1467 was safe and well-tolerated in a group of 6 patients with SPMS, up to a dose of 800 µg. Conclusions: The results of this study support further development of ATX-MS-1467 in a clinical trial powered to investigate the immunologic and clinical benefits of treatment in relapsing-remitting MS. Classification of evidence: This study provides Class IV evidence that ATX-MS-1467 is safe and tolerated in a group of 6 patients with SPMS.